Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Experience the convenience of finding accurate answers to your questions from knowledgeable professionals on our platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
Sure, let's solve the equation [tex]\(\log_7(3x^3 + x) - \log_7(x) = 2\)[/tex] step-by-step and identify any extraneous solutions.
First, let's use the properties of logarithms to combine the logarithms:
[tex]\[ \log_7(3x^3 + x) - \log_7(x) = \log_7\left(\frac{3x^3 + x}{x}\right) = \log_7(3x^2 + 1) \][/tex]
So, the equation simplifies to:
[tex]\[ \log_7(3x^2 + 1) = 2 \][/tex]
To clear the logarithm, rewrite the equation in exponential form:
[tex]\[ 3x^2 + 1 = 7^2 \][/tex]
Since [tex]\(7^2 = 49\)[/tex], the equation becomes:
[tex]\[ 3x^2 + 1 = 49 \][/tex]
Now, solve for [tex]\(x\)[/tex]:
[tex]\[ 3x^2 + 1 = 49 \][/tex]
[tex]\[ 3x^2 = 48 \][/tex]
[tex]\[ x^2 = 16 \][/tex]
[tex]\[ x = \pm 4 \][/tex]
So, the potential solutions are [tex]\(x = 4\)[/tex] and [tex]\(x = -4\)[/tex].
Next, we should check for extraneous solutions. A solution is extraneous if it does not satisfy the original equation or if it makes the argument of any logarithm non-positive (since logarithms of non-positive numbers are undefined).
Let's check both solutions:
1. For [tex]\(x = 4\)[/tex]:
[tex]\[ \log_7(3(4)^3 + 4) - \log_7(4) = 2 \][/tex]
[tex]\[ \log_7(3 \cdot 64 + 4) - \log_7(4) = 2 \][/tex]
[tex]\[ \log_7(192 + 4) - \log_7(4) = 2 \][/tex]
[tex]\[ \log_7(196) - \log_7(4) = 2 \][/tex]
[tex]\[ \log_7\left(\frac{196}{4}\right) = 2 \][/tex]
[tex]\[ \log_7(49) = 2 \][/tex]
Since [tex]\(7^2 = 49\)[/tex], this is true, so [tex]\(x = 4\)[/tex] is a valid solution.
2. For [tex]\(x = -4\)[/tex]:
Check the arguments of the logarithms:
[tex]\[ \log_7(3(-4)^3 + (-4)) - \log_7(-4) \][/tex]
[tex]\[ 3(-64) + (-4) = -192 - 4 = -196 \][/tex]
Since [tex]\(\log_7(-196)\)[/tex] and [tex]\(\log_7(-4)\)[/tex] are undefined (logarithms of negative numbers are undefined in the real number domain), [tex]\(x = -4\)[/tex] is not a valid solution. Therefore, [tex]\(x = -4\)[/tex] is extraneous.
Considering this, the extraneous solution to the given logarithmic equation is:
[tex]\[ x = -4 \][/tex]
First, let's use the properties of logarithms to combine the logarithms:
[tex]\[ \log_7(3x^3 + x) - \log_7(x) = \log_7\left(\frac{3x^3 + x}{x}\right) = \log_7(3x^2 + 1) \][/tex]
So, the equation simplifies to:
[tex]\[ \log_7(3x^2 + 1) = 2 \][/tex]
To clear the logarithm, rewrite the equation in exponential form:
[tex]\[ 3x^2 + 1 = 7^2 \][/tex]
Since [tex]\(7^2 = 49\)[/tex], the equation becomes:
[tex]\[ 3x^2 + 1 = 49 \][/tex]
Now, solve for [tex]\(x\)[/tex]:
[tex]\[ 3x^2 + 1 = 49 \][/tex]
[tex]\[ 3x^2 = 48 \][/tex]
[tex]\[ x^2 = 16 \][/tex]
[tex]\[ x = \pm 4 \][/tex]
So, the potential solutions are [tex]\(x = 4\)[/tex] and [tex]\(x = -4\)[/tex].
Next, we should check for extraneous solutions. A solution is extraneous if it does not satisfy the original equation or if it makes the argument of any logarithm non-positive (since logarithms of non-positive numbers are undefined).
Let's check both solutions:
1. For [tex]\(x = 4\)[/tex]:
[tex]\[ \log_7(3(4)^3 + 4) - \log_7(4) = 2 \][/tex]
[tex]\[ \log_7(3 \cdot 64 + 4) - \log_7(4) = 2 \][/tex]
[tex]\[ \log_7(192 + 4) - \log_7(4) = 2 \][/tex]
[tex]\[ \log_7(196) - \log_7(4) = 2 \][/tex]
[tex]\[ \log_7\left(\frac{196}{4}\right) = 2 \][/tex]
[tex]\[ \log_7(49) = 2 \][/tex]
Since [tex]\(7^2 = 49\)[/tex], this is true, so [tex]\(x = 4\)[/tex] is a valid solution.
2. For [tex]\(x = -4\)[/tex]:
Check the arguments of the logarithms:
[tex]\[ \log_7(3(-4)^3 + (-4)) - \log_7(-4) \][/tex]
[tex]\[ 3(-64) + (-4) = -192 - 4 = -196 \][/tex]
Since [tex]\(\log_7(-196)\)[/tex] and [tex]\(\log_7(-4)\)[/tex] are undefined (logarithms of negative numbers are undefined in the real number domain), [tex]\(x = -4\)[/tex] is not a valid solution. Therefore, [tex]\(x = -4\)[/tex] is extraneous.
Considering this, the extraneous solution to the given logarithmic equation is:
[tex]\[ x = -4 \][/tex]
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.